Helge Nielsen (red.): Køge bys historie 1288-1988. Bd. I:1288- bd. II: 1850-1988. (Køge Kommune, Køge Museum og Køge Byhistoriske Arkiv, 1985 og 1988). Bd. I: 416 s., 495,- kr., bd. II: 432 s., 525,- kr. - Sode-Madsen, Hans (Historie/Jyske Samlinger, 1989)
-